2020
DOI: 10.3389/fnbeh.2020.588400
|View full text |Cite
|
Sign up to set email alerts
|

Turning the ′Tides on Neuropsychiatric Diseases: The Role of Peptides in the Prefrontal Cortex

Abstract: Recent advancements in technology have enabled researchers to probe the brain with the greater region, cell, and receptor specificity. These developments have allowed for a more thorough understanding of how regulation of the neurophysiology within a region is essential for maintaining healthy brain function. Stress has been shown to alter the prefrontal cortex (PFC) functioning, and evidence links functional impairments in PFC brain activity with neuropsychiatric disorders. Moreover, a growing body of literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 290 publications
(377 reference statements)
0
34
0
Order By: Relevance
“…(G) Binge drinking reduces current-induced spiking in female SST PL neurons (DID: n = 12 cells, control: n = 9 cells, F current (20,380) = 39.339, p < 0.001; F binge (1,19) = 5.754, p = 0.027, F current x binge (20,380) = 0.995, p = 0.467)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(G) Binge drinking reduces current-induced spiking in female SST PL neurons (DID: n = 12 cells, control: n = 9 cells, F current (20,380) = 39.339, p < 0.001; F binge (1,19) = 5.754, p = 0.027, F current x binge (20,380) = 0.995, p = 0.467)…”
Section: Resultsmentioning
confidence: 99%
“…Here we did not assess whether the effects of hM3Dq-induced excitation of PL SST neurons on alcohol binge drinking could be partially attributed to SST peptide release and SST signaling in the PL. The neuropeptide SST has been shown to act largely via a family of Gi/o-coupled receptors (SSTR1-5) to inhibit neuronal excitability (18,19). 0.066, p = 0.798, Fsex x binge(1,39) = 1.704, p = 0.199) (K) Binge drinking did not alter sIPSC frequency in SST cells (control male: n = 11 cells, DID male: n = 10 cells, control female: n = 9 cells, DID female: n = 11 cells; Fsex(1,37) = 0.021, p = 0.884; Fbinge(1,37) = 0.152, p = 0.698, Fsex x binge(1,37) = 3.232, p = 0.080).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmaceuticals 2021, 14, 643 2 of 13 While several studies have shown that some of the classical neurotransmitters play an important role in cognitive flexibility [12,[19][20][21], the role of neuropeptides in cognitive flexibility is poorly understood. This is surprising, since terminals and receptors of different neuropeptides are (1) localized within the regions of the frontal cortex involved in cognitive flexibility, and (2) down-regulated in neuropsychiatric disorders which are associated with deficits in cognitive flexibility [22]. One exception is probably the neuropeptide orexin, whose levels in the cerebrospinal fluid are upregulated in those schizophrenia patients with fewer negative and disorganized symptoms [23], and for which there is some research regarding its role in cognitive flexibility [24,25].…”
Section: Introductionmentioning
confidence: 99%